Lower grass stomatal conductance under elevated CO2 can decrease transpiration and evapotranspiration rates despite carbon fertilization - Sate Ahmad; Charilaos Yiotis; Weimu Xu; Jan Knappe; Laurence Gill; Jennifer McElwain (Plant Direct)
Abstract Anthropogenic increase in carbon dioxide (CO2) affects plant physiology. Plant responses to elevated CO2 typically include: (1) enhanced photosynthesis and increased primary productivity due to carbon fertilization and (2) suppression of leaf transpiration due to CO2‐driven decrease in stomatal conductance. The combined effect of these responses on the total plant transpiration and on evapotranspiration (ET) has a wide range of implications on local, regional, and global hydrological cycles, and thus needs to be better understood. Here, we investigated the net effect of CO2‐driven perennial ryegrass (Lolium perenne) physiological responses on transpiration and evapotranspiration by integrating physiological and hydrological (water budget) methods, under a controlled environment. Measurements of the net photosynthetic rate, stomatal conductance, transpiration rate, leaf mass per area, aboveground biomass, and water balance components were recorded. Measured variables under elevated CO2 were compared with those of ambient CO2. As expected, our results show that elevated CO2 significantly decreases whole‐plant transpiration rates (38% lower in the final week) which is a result of lower stomatal conductance (57% lower in the final week) despite a slight increase in aboveground biomass. Additionally, there was an overall decline in evapotranspiration (ET) under elevated CO2, indicating the impact of CO2‐mediated suppression of transpiration on the overall water balance. Although studies with larger sample sizes are needed for more robust conclusions, our findings have significant implications for global environmental change. Reductions in ET from ryegrass‐dominated grasslands and pastures could increase soil moisture and groundwater recharge, potentially leading to increased surface runoff and flooding.